Does price regulation affect atorvastatin sales in India? An impact assessment through interrupted time series analysis. Issue 1 (24th January 2019) - Selvaraj, Sakthivel; Farooqui, Habib Hasan; Mehta, Aashna
Abstract : Objective: The objective of this study was to examine the impact of medicines price regulation (Drug Price Control Order, 2013) on the market share of atorvastatin in the Indian retail market for statins. Setting: All Indian states, January 2012 to December 2015. Design: Quasi-experimental—interrupted time series analysis. Data: Pharmaceutical sales audit data set from IMS Health (now IQVIA) for the 48-month period from January 2012 to December 2015. Outcome measure: Share of atorvastatin (in percentage) in the Indian market for statins in terms of sales volumes. Results: We observed that the price regulation notification (Drug Price Control Orders, 2013) was associated with 0.12% (p<0.001; 95% CI 0.06 to 0.18) increase in the trend of the average monthly market share of atorvastatin (5 mg and 10 mg). After 31 months of price ceilings notification, the average market share of atorvastatin was 3.41% higher than would have been expected had the price ceilings not been notified. In sensitivity analysis, with a control, our findings remain robust, we observed a 0.16% (p<0.001; 95% CI 0.08 to 0.24) rise in the trend of average monthly market share of atorvastatin (5 mg and 10 mg) as compared with the change in the control. Conclusions: Price control as a public intervention did improve the relative sales of atorvastatin in the statin market in India.